Differential activation of Fyn kinase distinguishes saturated and unsaturated fats in mouse macrophages. - Tarabra, E; An Lee, T; Zammit, V; Vatish, M; Yamada, E; Pessin, J; Bastie, C (Impact Journals, 2017)
Diet-induced obesity is associated with increased adipose tissue activated macrophages. Yet, how macrophages integrate fatty acid (FA) signals remains unclear. We previously demonstrated that Fyn deficiency (fynKO) protects against high fat diet-induced adipose tissue macrophage accumulation. Herein, we show that inflammatory markers and reactive oxygen species are not induced in fynKO bone marrow-derived macrophages exposed to the saturated FA palmitate, suggesting that Fyn regulates macrophage function in response to FA signals. Palmitate activates Fyn and re-localizes Fyn into the nucleus of RAW264.7, J774 and wild-type bone marrow-derived macrophages. Similarly, Fyn activity is increased in cells of adipose tissue stromal vascular fraction of high fat-fed control mice, with Fyn protein being located in the nucleus of these cells. We demonstrate that Fyn modulates palmitate-dependent oxidative stress in macrophages. Moreover, Fyn catalytic activity is necessary for its nuclear re-localization and downstream effects, as Fyn pharmacological inhibition abolishes palmitate-induced Fyn nuclear redistribution and palmitate-dependent increase of oxidative stress markers. Importantly, mono-or polyunsaturated FAs do not activate Fyn, and fail to re-localize Fyn to the nucleus. Together these data demonstrate that macrophages integrate nutritional FA signals via a differential activation of Fyn that distinguishes, at least partly, the effects of saturated versus unsaturated fats.